Nintedanib allows retreatment with atezolizumab of combined non-small cell lung cancer/idiopathic pulmonary fibrosis after atezolizumab-induced pneumonitis: a case report - Hideaki Yamakawa; Tomohiro Oba; Hiroki Ohta; Yuta Tsukahara; Gen Kida; Emiri Tsumiyama; Tomotaka Nishizawa; Rie Kawabe; Shintaro Sato; Keiichi Akasaka; Masako Amano; Kazuyoshi Kuwano; et al. (BMC Pulmonary Medicine, 2019)
Abstract Background Nintedanib is a tyrosine kinase inhibitor that efficiently slows the progression of idiopathic pulmonary fibrosis (IPF) and has an acceptable tolerability profile. In contrast, immune checkpoint inhibitors (ICIs) such as programmed death 1 and programmed death ligand 1 inhibitors have shown clinical activity and marked efficacy in the treatment of non-small cell lung cancer. However, it is unclear whether nintedanib reduces the risk of ICI-induced pneumonitis in IPF. Case presentation A 78-year-old man with squamous cell lung carcinoma in IPF underwent second-line treatment with pembrolizumab. He was diagnosed as having pembrolizumab-induced pneumonitis after two cycles. He was administered prednisolone (PSL) and then improved immediately. Thereafter, his lung cancer lesion enlarged despite treatment with TS-1. Atezolizumab was then administered as 4th-line chemotherapy, but he immediately developed atezolizumab-induced pneumonitis after 1 cycle. The re-escalated dosage of PSL improved the pneumonitis, and then nintedanib was started as additional therapy. Under careful observation with nintedanib, atezolizumab was re-administered on day 1 of an every-21-day cycle. After three cycles, it remained stable without exacerbation of drug-induced pneumonitis. Conclusion This case indicates the possibility that the addition of nintedanib to ICI therapy might prevent drug-induced pneumonitis or acute exacerbation of IPF. However, whether anti-fibrotic agents such as nintedanib are actually effective in preventing ICI-induced pneumonitis in ILD remains unknown and additional research is greatly needed to identify effective therapies for ILD combined with lung cancer.